Fiscal Sustainability Analysis in Managing State Debt - Leonardo, Dominikus; Thomas, Fransiskus (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2024)
To maintain fiscal sustainability when the state budget is in deficit, the government issues debt, which has the potential to burden the state budget. This study examines fiscal sustainability as observed through debt management, which is represented by the primary balance/GDP ratio and the debt to GDP ratio, which is influenced by macroeconomic variables such as interest rates, economic growth, inflation, and exchange rate changes. The results of the variance decomposition show that the condition of the primary balance/GDP ratio is a factor that determines changes in the debt to GDP ratio. The results of the impulse response function show that fiscal sustainability occurs when the primary balance/GDP ratio is in surplus so that it can reduce the debt to GDP ratio. Conversely, increasing the debt to GDP ratio can support the primary balance/GDP ratio to achieve a surplus or reduce a deficit. Based on the VAR estimation results, to maintain fiscal sustainability, the government needs to pay attention to four aspects that could affect relative costs, such as economic growth, interest rates, inflation, and changes in exchange rates. Macroeconomic developments need attention because this variable can affect spending quality and debt management in the state budget.